Pengembangan Aplikasi Front-End dan Back-End CHEPI (Checklist Peralatan I Gusti Ngurah Rai) Berbasis Mobile - Ramadhana Nasution, Aulia (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2018)
PT. (Persero) Angkasa Pura I conducts management (exploitation, development, and utilization) of airports and surrounding areas in a good and innovative manner, so that optimal utilization is achieved and results can be used to grow the company which ultimately contributes to the benefits of the State and Development National. Making a CHEPI application based on Mobile because it does not have its own application to Scan QR Code and still use the Scan QR Code feature from the Line application when checking items that make technicians trouble in checking because it uses a web-based CHEPI that does not have a QR Scan feature Code. The CHEPI application uses the Android Studio JAVA and PHP programming languages ??to build mobile-based applications and utilize MySQL databases. The development of Back-End from the CHEPI application will include analysis of system requirements, system design with Use Case Diagrams, Class Diagrams, Entity-Relationship Diagrams (ERD), and also the implementation of features. With this CHEPU application, it is expected to be able to assist in the process of checking goods at each department.